2003
DOI: 10.1159/000074045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treadmill Exercise on Circulating Thyroid Hormone Measurements

Abstract: Objectives: Effects of exercise on circulating thyroid hormone (TH) values remain controversial. We sought to observe the effect of treadmill exercise on serum TH values in highly selected subjects. Methods: Twenty-six healthy male military recruits aged 23–27 (mean, 25) years were studied. All had maintained identical diet and physical activity for a week before the test. Serum samples were drawn before (baseline) and immediately, 1, 4, 24, 24 and 48 h after maximal exercise (on a treadmill, Bruce protocol). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 15 publications
(39 reference statements)
2
25
0
Order By: Relevance
“…In Huang et al (2004) research, Twenty-six healthy male military recruits aged 23 to 27 years with a mean of 25 years have been studied. All subjects had maintained identical diet and physical activity for a week before the test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Huang et al (2004) research, Twenty-six healthy male military recruits aged 23 to 27 years with a mean of 25 years have been studied. All subjects had maintained identical diet and physical activity for a week before the test.…”
Section: Resultsmentioning
confidence: 99%
“…No significant changes of serum mean TH values before and after exercise have been found except for TSH, which had increased significantly immediately after exercise (1.72 vs. baseline 1.42 IU/L, p < 0.01). They have reported that maximal treadmill exercise had not greatly affected the determination of concentrations of circulating THs (Huang et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…From a large number of studies exploring the relationship between exercise and testosterone, no definite conclusion can be drawn [12][13][14]. Bosco et al [15] reported that short-term strenuous exercise increased total and free testosterone levels by 12% and 13%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, leptin and cytokines secreted from fat tissues affect the levels of cortisone, testosterone, thyroid, and growth hormones [2,3]. In various studies investigating the relationship between exercise and hormones, different results were obtained [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…From a large number of studies exploring the relationship between exercise and hormones, no definite conclusion can be drawn [4][5][6]. Short-term strenuous exercise increased total and free testosterone levels by 12% and 13%, respectively [7].…”
Section: Introductionmentioning
confidence: 99%